Preferred and Actual Opinions toward Inquiry-based Instruction of Primary Science Teachers in the Northeast of Thailand - Nuangchalerm, Prasart; Prachagool, Veena (Jurnal Penelitian dan Pembelajaran IPA, 2019)
Inquiry-based instruction is widely used in science classrooms. It helps students and teachers employed student-centered approach as well as the advancements of academic development. This study explored preferred and actual opinions of 545 primary science teachers toward inquiry-based instruction. They were asked preferred and actual opinions through five components of inquiry-based instruction during workshop on active learning from 5 provinces. Data were collected through teachers’ inquiry-based instruction questionnaires. Data were analyzed by mean, standard deviation, and percentage, also Pearson correlation was used for seeking its correlational significance. The findings showed that teachers had preferred and actual opinions of teachers toward inquiry-based instruction at high level. Also, phases of instruction, preferred and actual opinions are positively correlated. The findings need to be more discussed how teachers implement inquiry-based learning to their students in the classroom contexts.